2020
DOI: 10.3390/md18080406
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Astaxanthin Micro/Nanoencapsulation to Improve Its Stability and Functionality as a Food Ingredient

Abstract: Astaxanthin is a carotenoid produced by different organisms and microorganisms such as microalgae, bacteria, yeasts, protists, and plants, and it is also accumulated in aquatic animals such as fish and crustaceans. Astaxanthin and astaxanthin-containing lipid extracts obtained from these sources present an intense red color and a remarkable antioxidant activity, providing great potential to be employed as food ingredients with both technological and bioactive functions. However, their use is hindered by: their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 139 publications
0
51
0
Order By: Relevance
“…Generally, the release of an active substance from a polymer matrix can be categorized in three main processes: (i) diffusion from a non-degraded polymer (diffusion-controlled system); (ii) enhanced drug diffusion due to polymer swelling (swelling-controlled system); (iii) release via polymer degradation and erosion (erosion-controlled system) [ 38 ]. Since the carriers used in this study were fully water soluble (at 30 °C), it can be concluded that the AST release was mainly controlled by an erosion-driven process.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the release of an active substance from a polymer matrix can be categorized in three main processes: (i) diffusion from a non-degraded polymer (diffusion-controlled system); (ii) enhanced drug diffusion due to polymer swelling (swelling-controlled system); (iii) release via polymer degradation and erosion (erosion-controlled system) [ 38 ]. Since the carriers used in this study were fully water soluble (at 30 °C), it can be concluded that the AST release was mainly controlled by an erosion-driven process.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to our results, astaxanthin in raw salmon flesh and supplements is relatively stable during in vitro digestion. Nonetheless, the bioaccessibility of carotenoids is also associated with their origin and chemical characteristics [ 37 ]. Many studies have focused on the increased stability of astaxanthin using different matrix formulations to protect the molecule in the gastrointestinal environment [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the bioaccessibility of carotenoids is also associated with their origin and chemical characteristics [ 37 ]. Many studies have focused on the increased stability of astaxanthin using different matrix formulations to protect the molecule in the gastrointestinal environment [ 37 , 38 , 39 ]. During lactic acid fermentation of shrimp waste, astaxanthin from fermented liquor is found in the free or esterified form [ 15 , 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some foods or their volatile compounds have already been encapsulated to mask undesirable flavors and odors: (i) pea protein ( Cui, Kimmel, Zhou, Rao, & Chen, 2020 ); (ii) oils in general (fish, shrimp, cod liver, garlic, green coffee, etc.) ( Gulzar & Benjakul, 2020 ; Morsy & Elsabagh, 2021 ; Oliveira et al, 2020 ; Pourashouri, Shabanpour, Heydari, & Raeisi, 2021 ; Raeisi, Ojagh, Pourashouri, Salaün, & Quek, 2021 ; Serfert, Drusch, & Schwarz, 2010 ); (iii) astaxanthin ( Martínez-Álvarez, Calvo, & Gómez-Estaca, 2020 ); (iv) catechin ( Astray, Mejuto, & Simal-Gandara, 2020 ); (v) bitter acids (caffeine, quinine, and chlorogenic) ( Astray et al, 2020 ); (vi) bioactive peptide powder ( Wang & Selomulya, 2020 ), among others. Currently, there are no products developed by the industry or described in the literature concerning flavor and aroma encapsulation for consumers with dysosmia and dysgeusia.…”
Section: Challenges and Future Trendsmentioning
confidence: 99%